Understanding the Hemodynamic Response and Sensory Contributions to Automatic Postural Control - St-Amant, Gabrielle (Université d'Ottawa / University of Ottawa, 2019)
The postural control-cognition dual-task literature has demonstrated greater postural stability through the examination of multiple kinetic and kinematic measures. Recently, sample entropy (SampEn) and wavelet discrete transform have supported the claim of automaticity, as higher SampEn values and a shift toward higher contribution from automatic sensory systems have been demonstrated in dual-task settings. In order to understand the cortical component of postural control, functional near-infrared spectroscopy (fNIRS) has been used to identify cortical activation under postural control conditions. However, the neural correlates of automatic postural behaviour have yet to be fully investigated. Therefore, the purpose of this study is to confirm the presence of automatic postural control through static and dynamic measurements, and to investigate the prefrontal cortex activation (PFC) when concurrently performing quiet standing and auditory cognitive tasks. Eighteen healthy young adults (21,4 ± 3,96yo), 12 females and 6 males, with no balance deficits were recruited. Participants were instructed to either quietly stand on a force platform (SM), perform three cognitive tasks while seated (SC) and perform a combination of SM and SC concurrently (DT). Results revealed automatic postural control as evidenced by lower area and standard deviation of center-of-pressure in DT conditions. As for SampEn and the wavelet analysis, greater values and a shift from vision to the cerebellum contribution were demonstrated in DT conditions. For the DNS task, a trend toward significantly lower right hemisphere PFC activation compared to left hemisphere activation in DT was evidenced, which potentially reiterate the presence of automaticity. Therefore, as demonstrated by this experiment, the simultaneous performance of a difficult cognitive task and posture yields automatic postural behaviour, and provides insight into the neural correlates of automaticity.
Keywords: Automatic Postural Control; Functional Near-Infrared Spectroscopy; Wavelet Discrete Transform; Sample Entropy; Dual-task